PROFILE OF GRADIENT PROCEPT AND STRAIGHT LINE EQUATIONS FOR JUNIOR HIGH SCHOOL STUDENTS BASED ON MATHEMATICS ABILITY - Prayogo, Prayogo; Suwarsono, St.; Khabibah, Siti (Journal of Honai Math, 2021)
AÂ proceptÂ is a combination of mental objects consisting of processes, concepts resulting from these processes, and symbols used to represent either concepts or processes. This study aims to describe the procept profile of the gradient concept and the equation of a straight line for the students of SMPN 1 Sooko Mojokerto. This type of research is descriptive qualitative exploratory. Determining the research subjects was carried out by giving a mathematical ability test to 42 prospective subjects, to obtain 5 students with high mathematics abilities, 22 students, and 15 low students, then from each category one research subject was taken. Data was collected using task-based interviews and analyzed by qualitative data analysis techniques through data reduction, data presentation, and conclusion drawing. The results showed that there were differences in the procept profile of the gradient and straight-line equations between students with high, medium, and low abilities. The procept profiles of students with high math abilities meet all categories, students with moderate math abilities meet most of the categories, and students with low math abilities meet the small categories of gradient and straight-line equations.